Examining the impact of cultural literacy on students’ attitudes of tolerance towards diversity - Nirmayani, L. Heny; Lasmawan, I Wayan; Suastika, I Nengah; Margunayasa, I Gede (Edelweiss Applied Science and Technology, 2024)
This study aims to identify the influence of cultural literacy on students’ understanding of attitudes of tolerance towards diversity. This quasi-experimental study was conducted using a post-test-only control group design. This study was conducted in an elementary school in Bali involving groups of fourth-grade students, who were students from two different classes and selected using statistical matching techniques. One group became the experimental group, and the other became the control group. The research data were collected using an understanding test of attitudes of tolerance towards diversity. The post-test was given to the two groups after the experimental group had been taught cultural literacy, and the control class was taught using conventional materials commonly used by teachers for eight meetings. The results of the post-test were analyzed quantitatively using descriptive statistics, independent t-test, and Cohen’s d. From the results of the descriptive statistical analysis, it was found that students in the control class had better average scores in terms of understanding attitudes of tolerance towards diversity than the control group. The results of the independent t-test showed that the difference in the average value was proven to be significant. Furthermore, the results of the effect size test also showed that cultural literacy has a large and significant influence on students’ understanding of attitudes of tolerance towards diversity. Thus, from these results, it can be concluded that cultural literacy is effective in improving students’ understanding of attitudes of tolerance towards diversity.